Inter-device reproducibility of retrobulbar blood flow velocity measurements in healthy subjects using color Doppler imaging - Vercellin Alice C., Verticchio (J Ultrasound, 2016)
PURPOSE: To evaluate the inter-device reproducibility of retrobulbar blood flow measurements obtained by two commercially available CDI (color Doppler imaging) devices. METHODS: The right eyes of 10 healthy volunteers were investigated. Four examiners, namely two ophthalmologists and two radiologists, performed CDI examination of the ophthalmic artery, central retinal artery and temporal short posterior ciliary arteries using both CDI devices: ESAOTE MYLAB™ and SIEMENS ANTARES STELLAR PLUS™. The peak systolic velocity (PSV), the end-diastolic velocity (EDV) and the resulting resistivity index (RI) were averaged for 3 cardiac cycles. To evaluate the reproducibility between both device measurements, the Lin’s concordance correlation coefficient (CCC) was used. CCC can be expressed as the product of Pearson’s r (the measure of precision) and C_b (the measure of accuracy). RESULTS: Results show that the inter-device reproducibility for CDI measurements is not acceptable since a poor degree of overall concordance (0.15<CCC<0.37) was obtained: accuracy was high (C_b > 0.71) but overall precision low (0.18< Pearson’s r <0.47). Ophthalmologists and radiologists obtained similar results. CONCLUSIONS: To evaluate the causal role of blood flow abnormalities in glaucoma, CDI analysis using different devices seems unreliable. CDI inter-device reproducibility seems unrelated to medical speciality of the examiners. However, to improve present results, the use of similar probes and standardized CDI instrument settings as well as a CDI images analysis by a single grader, might possibly improve the inter-device reproducibility when testing the retrobulbar blood flow velocity.